Implementation of Leaders' Policy in the Development of UMKM in the Cibeureum District - khadafi, Muhammad; Saepudin, Asep; Kamarubiani, Nike (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The existence of MSMEs cannot be eliminated or avoided from today's nation's society. Cibeureum Village is one of the sub-districts in Cimahi Selatan District, Cimahi City, West Java, Indonesia which has a population of 61,027 people, consisting of 30,797 men and 30,230 women. The livelihoods of the Cibeureum sub-district community are varied, while the livelihoods are as civil servants, traders, craftsmen, private employees and others. Cibeureum sub-district, there are 24 MSMEs registered to date, in which conditions the Cibeureum MSMEs have an entrepreneurial tendency, they are still individual and still lack collaboration, many MSMEs do not have complete administration, conventional and digital product marketing is still not optimal, capital is still independent, there is no grouping of types of business and product development innovation is still not maximized. This descriptive qualitative research uses a phenomenological approach. The phenomenological method seeks to understand the meaning of events and their relation to people who are in certain situations. The result of this research is a new innovation in the form of a sustainable assistance model to optimize MSMEs in Cibeureum Village. This innovation is expected to have an impact on increasing economic welfare through MSMEs.Keywords: SMEs, Policy